The impact of diabetes on the urinary system and the need for preventive strategies, early detection, and management of urological complications - Kumar, N. Anil; Kumar, Shashi; Reddy, C. Konda; Suseel, N. Anirudh (Orapuh Journal, 2024)
IntroductionDiabetes mellitus affects many organ systems, including the urinary system. Because of this, it is a worldwide public health issue. This study is about urological problems that can happen with diabetes. The main goals of management are prevention, early detection, and treatment.PurposeThis study aimed to investigate the impact of diabetes on the urinary system.Methods125 diabetics who attended Sri Venkateswara Institute of Medical Sciences, Tirupati, Andhra Pradesh, India between 2019 and 2021 participated in this retrospective study. We looked at their demographic information and the frequency of urological problems and the associated preventive strategies. Chi-square testing was used for statistical analyses.ResultsThe most commonly occurring urological problems among the study participants were urinary tract infections (20%), diabetic nephropathy (32%), neurogenic bladder failure (12%), or impotence (24%). We also observed that the introduction of different preventative strategies into the management of the referent participants stemmed the progression of the problem in varying degrees. ConclusionThe study has identified commonly diagnosed urological problems among the participants and demonstrated the importance of early detection and preventative strategies to improve patient outcomes and treatment.